Avaliação de mastócitos em cistos periapicais, cistos dentígeros e tumores odontogênicos ceratocísticos - Netto, Juliana de Noronha Santos (2011)
Mast cells are found in the connective tissue and can participate in acute and chronic inflammatory responses and induce early and also late-phase reactions. Mast cells are distributed in odontogenic cysts and tumors and it has been suggested that mast cell degranulation products can be related to matrix degradation in the cystic or tumor and to the production of cytokines, which appear to have important functions in bone resorption and cystic growth. The aim of this study was to evaluate the frequency and distribution of mast cells in periapical and dentigerous cysts, and keratocystic odontogenic tumors. Paraffin embedded specimens from 20 periapical cysts, 20 dentigerous cysts (14 with and six without inflammation) and 20 keratocystic odontogenic tumors (16 with and four without inflammation) were selected from the files of the Department of Pathology of the Antonio Pedro Universitary Hospital/Fluminense Federal University. Hematoxylin and eosin stained slides were reviewed through optical microscopy in all cases for diagnosis confirmation by light microscopy. Demographic, clinical and radiographic data from all cases were retrieved from the laboratory records. For observation of mast cells, all 60 cases were evaluated through toluidine blue staining and immunohistochemical reaction with antibody directed against mast cell tryptase. Mast cells were quantified using the Image Pro-Plus 4.5 program (Media Cybernetics, USA) by two techniques in 10 high power fields (40x) and was obtained the mean number of mast cells in three locations: epithelial, superficial fibrous wall and deep fibrous wall. The mean number of mast cells in each region was compared in the three groups of lesions and also was compared the mean number between the different locations to each one of the lesions studied, giving their quantification and distribution profile and descriptive comparison. The distribution of mast cells evaluated through immunohistochemistry was higher in the group of inflamed dentigerous cysts (2,9 cells/high power field), followed by periapical cysts (1,5 cells/high power field), inflamed keratocystic odontogenic tumor (1,3 cells/high power field) and non inflamed dentigerous cysts (0) and non inflammed keratocystic odontogenic tumor (0). In contrast, the distribution of mast cells observed through immunohistochemistry revealed that periapical cysts showed the higher mean (5,3 cells/high power field), followed by inflamed dentigerous cysts (4,7 cells/high power field), inflamed keratocystic odontogenic tumor (3,7 cells/high power field), non inflamed keratocystic odontogenic tumor (2 cells/high power field) and non inflamed dentigerous cyst (0,9 cells/high power field). The deep portion of the fibrous wall presented the higher mean of the mast cells in the three groups of lesions studied, through both techniques, in comparison to the epithelial and superficial regions, except for the non inflamed keratocystic odontogenic tumor analyzed through immunohistochemistry, which showed a higher number of mast cells in the superficial region of the fibrous wall. The increased number of mast cells in lesions with inflammation and at sities of inflammation indicates the participation of these cells in the inflammatory response. The predominance of mast cells, a lot of them degranulated, in the deep region of the fibrous cystic wall may suggest a higher cellular activity possibly related to bone resorption and growth of these lesions. More studies investigating the mediators of inflammation and bone resorption are needed to confirm the role of mast cells in the pathogenesis and behavior of the cystic lesions